Criteria of ideal diagnostic method in neurosurgery - Leonid B. Likhterman (LLC "MEDIAFORMAT", 2023)
The criteria of ideal diagnostic method in neurosurgery were first developed based on studying the hundred-year history of the brain and spinal cord disorder recognition development. Among these such characteristics, as remote visualization, safety, and accessibility are decisive. The today's leaders that are most close to the ideal method are as follows: thermal imaging, ultrasound tomography, X-ray computed tomography, magnetic resonance imaging and its modifications.